Influence of non-radiative exciton recombination in silicon on photoconversion efficiency. 2. Short Shockley–Read–Hall lifetimes - A.V. Sachenko; V.P. Kostylyov; V.M. Vlasiuk; R.M. Korkishko; I.O. Sokolovskyi; V.V. Chernenko; M.A. Evstigneev (Semiconductor Physics, Quantum Electronics & Optoelectronics, 2017)
The influence of non-radiative exciton recombination (NRER) on the photoconversion efficiency in silicon solar cells with short Shockley–Read–Hall lifetimes τSRH has been studied. It has been shown that the efficiency reduction due to this effect is the stronger the shorter τSRH. The influence of NRER is most evident when the NRER time becomes shorter than τSRH. At sufficiently short τSRH, NRER substantially limits the optimal base doping levels of silicon solar cells, at which the photoconversion efficiency is maximal.